Adverse Events in Infants Less Than 6 Months of Age After Ambulatory Surgery and Diagnostic Imaging Requiring Anesthesia. Issue 4 (1st July 2022) - Uffman, Joshua C.; Kim, Stephani S.; Quan, Loan N.; Shelton, Thomas; Beltran, Ralph J.; Jatana, Kris R.; Chiang, Tendy; Tobias, Joseph D.
Abstract : Introduction: AAP guidelines recommend infants less than 6 months of age are monitored for at least 2 hours following surgery. This retrospective study evaluated if adherence to the 2-hour monitoring guideline decreased the risk of adverse events associated with ambulatory procedures in infants younger than 6 months. Methods: We queried the hospital's electronic medical record to identify patients younger than 6 months of age who received anesthetic care from January 2015 to March 2020. Demographic data, intraoperative adverse events, and returns to the emergency department (ED) or urgent care within 7 days were captured for each patient. We calculated the number and frequency for categorical data and median and interquartile range (IQR) for continuous data. Chi-square or Fisher's exact test were used to compare patients who experienced an adverse event to those that did not. Results: One thousand one hundred seventy-seven patients who had 1, 261 unique anesthetic encounters were analyzed. Forty-four adverse events were identified, 20 (1.6%) before discharge, including 3 unplanned admissions, and 24 (1.9%) returns to the ED/UC within 7 days postoperatively. We did not observe differences in postoperative recovery time in patients who experienced an adverse event and those who did not (88 min vs. 77 min, respectively, P = 0.078). None of the ED/UC returns would have been avoided by a longer PACU stay. Conclusions: With the appropriate patient selection, once physiological discharge readiness is met, adherence to a strict 2-hour time-based discharge criteria does not increase safety for infants younger than 6 months of age after ambulatory procedures.